Cloning and Expression of Recombinant Human Endostatin in Periplasm of Escherichia coli Expression System - Abbas Mohajeri; Yones Pilehvar-Soltanahmadi; Mohammad Pourhassan-Moghaddam; Jalal Abdolalizadeh; Pouran Karimi; Nosratollah Zarghami (Advanced Pharmaceutical Bulletin, 2016)
Purpose: Recombinant human endostatin (rhEs) is an angiogenesis inhibitor which is used as a specific drug in the treatment of non-small-cell lung cancer. In the current research, we developed an efficient method for expressing soluble form of the rhEs protein in the periplasmic space of Escherichia coli via fusing with pelB signal peptide.